Evaluation of Reverse Logistics in Challenges within the Manufacturing Pharmaceutical Companies - Mpho Sharon Makgedi Makaleng; Keith Richard Lambert (Ital Publication, 2021)
The link between reverse logistics and logistics is being increasingly noted by logistics experts and researchers globally, especially in manufacturing pharmaceutical companies. This has led to the examination of reverse logistics challenges in manufacturing pharmaceutical companies. The main objective was to examine reverse logistics challenges in manufacturing pharmaceutical companies in the City of Tshwane (South Africa). The study aimed to find approaches to deal with the challenges of reverse logistics such as gatekeeping, managerial implications, technology, waste elimination, transportation, and product recalls within the industry. The study was empirical, and a quantitative approach was used. Furthermore, data analysis was conducted by using the Stata V13 statistical software where a descriptive analysis was employed. Questionnaires were posted via SurveyMonkey to the staff at fifty pharmaceutical companies. This resulted in a total of 127 respondents, which provided a response rate of 51%. The findings indicated that manufacturing pharmaceutical companies face a variety of challenges; such as lack of skills and skills transfer, transport, and gatekeeping (amongst others), when dealing with reverse logistics. It is thus recommended that processes and strategies involved in reverse logistics should be known and taken into consideration because of the importance of reverse logistics in manufacturing pharmaceutical companies. Doi: 10.28991/esj-2021-01291 Full Text: PDF